1997
DOI: 10.1128/aem.63.8.2977-2982.1997
|View full text |Cite
|
Sign up to set email alerts
|

Amy as a reporter gene for promoter activity in Nocardia lactamdurans: comparison of promoters of the cephamycin cluster

Abstract: Promoter probe vectors containing the pA origin of replication and the Streptomyces griseus promoterless amy gene (encoding ␣-amylase) as reporter have been constructed to study transcription initiation regions in Nocardia lactamdurans. In some of the promoter probe vectors the phage fd terminator has been introduced to avoid readthrough expression from upstream sequences. By using these vectors, four different transcription initiation regions of the cephamycin gene cluster have been studied in N. lactamdurans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Two DNA fragments of 1.2 kb Kpn I– Sac II and 3.5 kb Sac I, both containing the tlrB gene (Fig. 1), were purified from the 5.5‐kb Bgl II fragment and subcloned in the bifunctional E. coli – Streptomyces plasmid pULVK99 [14] rendering pALF250 and pALF295, respectively (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two DNA fragments of 1.2 kb Kpn I– Sac II and 3.5 kb Sac I, both containing the tlrB gene (Fig. 1), were purified from the 5.5‐kb Bgl II fragment and subcloned in the bifunctional E. coli – Streptomyces plasmid pULVK99 [14] rendering pALF250 and pALF295, respectively (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…pBluescript I KS(+), pBluescript II SK(+) and pBC KS(+) phagemids (Stratagene) were utilized for routine subcloning and ssDNA preparation with the helper phage M13K07. pULVK99 [14] was used as E. coli – Streptomyces spp. shuttle vector and pSET152 [10] as intergeneric conjugation vector.…”
Section: Methodsmentioning
confidence: 99%
“…Two DNA fragments of 1.2 kb KpnI^SacII and 3.5 kb SacI, both containing the tlrB gene ( Fig. 1), were puri¢ed from the 5.5-kb BglII fragment and subcloned in the bifunctional E. coli^Streptomyces plasmid pULVK99 [14] rendering pALF250 and pALF295, respectively (Fig. 2).…”
Section: Construction Of Plasmids Carrying the Tlrb Genementioning
confidence: 99%
“…strain HR167 [16], Amycolatopsis mediterranei U-32 [11] and A. mediterranei strains DSM 40773, DSM 43304, MTCC 17 [4,12,14,17]. Several studies have demonstrated the utility of pA387-derived shuttle vectors [19][20][21][22][23][24]. However, relatively little is known regarding the genetic makeup of plasmid pA387.…”
Section: Introduction *mentioning
confidence: 99%